SIMULTANEOUS RELATIONSHIP BETWEEN LEVERAGE POLICY AND DIVIDEND POLICY - Purnamasari, Nadya; Muharam, Harjum (Faculty of Economics and Business Diponegoro University, 2016)
This study aims to analyze the simultaneous relationship between dividend policy and leverage policy along the factors influence them. Dividend policy is measured by dividend payout ratio, while leverage policy is measured by debt ratio. The factors influencing these two policies are profitability, size, asset structure, and growth. This study uses secondary data from Indonesia Stock Exchange (IDX), within companies that always listed on LQ45 Index during 2009 – 2014 are used as sample. Two stage least square (2SLS) is used as regression method. The result shows that both of two policies have simultaneous relation and give positive effect. Profitability gives positive effect, while size gives insignificant effect to dividend policy. Profitability and growth give negative effect, while asset structure gives insignificant effect to leverage policy.